The Effect of Using Phyto-Additives in the Nutrition of Broilers (Garlic, Pepper, Turmeric and Coriander) on Nutritional and Bioproductive Indices - Adrian Rășinar; Gabriel Alexandru Ioniță; Lavinia Ștef; Francois Djitie Kouatcho; Eliza Simiz (Scientific Papers Animal Science and Biotechnologies, 2023)
The prohibition of using antibiotics in the nutrition of chicken has led to the occurrence of a new category of additives knows as phytoadditives, which have antimicrobial, antioxidant, anti-inflammatory effects, as well as growth stimulation effects. Due to the contradictions in literature, further investigations are needed for the clarification of the different nutritional aspects of phytoadditives. This study was carried out by 60 broilers ROSS 308, in order to assess the effect of feed supplemented with garlic (Allium sativum), turmeric powder (Curcuma longa), black pepper (Piper nigrum) and coriander seeds (Coriandrum sativum) on nutritional and bioproductive indices of broilers. The treatments were: a control group received no supplements and four groups that got 1% of garlic (T1), 1% turmeric (T2), 1% pepper (T3) and 1% coriander (T4). The body weight at the end of the growth period was significantly higher (p<0.05) in chickens from T1 (garlic) 2833.50±55.449 grams as compared to that of chickens from T0 (control) 2489.00±70.092 grams and insignificantly bigger (p>0.05) as compared to T2, T3 and T4. The most efficient feed conversion index was present in T3 (pepper) 1.718±0.114. Supplementing the feed with phytoadditives has led to the improvement of the bioproductive performances.